Analisis Pelaksanaan Sistem dan Model Perencanaan Sumber Daya Manusia dalam Meningkatkan Potensi dan Kinerja BTN Syariah Cabang Tangerang - Aramita Dinah Idelia; Rizka Fathya Fancha; Muljadi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to determine the system and model of human resource planning at BTN Syariah Tangerang Branch. This research uses a descriptive qualitative approach. The results showed that the human resource planning process at BTN Syariah Tangerang Branch is carried out with two opportunities in obtaining qualified employees, namely through internal and external to determine future human resource needs and to ensure the quality required for each position by paying attention to understanding the principles of Islamic Sharia and Sharia products in funding and financing. Every human resource planning at BTN Syariah Tangerang Branch includes program planning activities related to the achievement of predetermined goals consistently such as internally seen from the KPI results of employee talent, SOPs and job descriptions and externally obtained from new recruits from the open labor market and human resource development programs through training